School Finance - A Policy Perspective - R. Odden Allan (MC Graw Hill, 2003)
Completely updated, 60% revised, this is a clear, concise discussion of how recent research in school finance, resource allocation and use for higher performance, site-based management of schools, and teacher compensation may impact the funding of our nation’s schools in the opening years of the new millenium. As a core text for all masters level students of educational administration, this text is the first to use computer simulations to extend the discussions of school finance formulas into the application stage. A password-required, user-friendly Microsoft Excel (PC and Mac) simulation, available at the McGraw-Hill School Finance Web site, for free download to adopters of the second edition, allows students to manipulate various school finance formulas and analyze their fiscal, political and equity impacts. This updated financial simulation (chapters 4 and 5 and Appendix) provides state data sets (for Illinois, Vermont, and Wisconsin) to allow for real-time comparisons of school finance equity across states. The last five chapters are thoroughly and substantially revised and describe current activities in school finance, recent research, and suggestions for the future. The second edition has revised discussions of important school finance issues: school finance litigation with an extended focus on adequacy (chapter 2), politics in the 1990s and its impact on school finance (chapter 6), allocation and use of educational resources (chapter 6), improving educational productivity (chapter 7), effective use of educational resources (chapter 8), school-based finance mechanisms (chapter 9), performance incentives (chapter 10), teacher compensation (chapter 11), and barriers to reform (chapter 12).